Parenting Patterns in Educating Children's Prayer Discipline During the Coronavirus Disease (Covid-19) - Imam Tabroni; Nano Munajat; Sanusi Uwes; Usep Dedi Rostandi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Children's discipline to perform the five daily prayers is often ignored by parents as the first educators at home during the Covid-19 pandemic. The purpose of this study was to determine parenting patterns in applying the discipline of five daily prayers to children during the Covid-19 pandemic. The research method used is qualitative. Data collection techniques are observation, interviews, and documentation. Triangulation data analysis. Research result; 1) invite children to pray as early as possible, 2) remind children at prayer times, 3) provide an understanding of the law of prayer. Appreciation is given by parents if the child prays on time. Warnings and guidance are applied if the child finds it difficult to pray on time. In addition to coaching and guidance, the application of the five prayers discipline also utilizes image media and visual audio. Manage playtime, study time, sleep time and prayer time